Low-pressure submerged membrane filtration for potential reuse of detergent and water from laundry wastewater - Bilad, M.R. (Elsevier Ltd, 2020)
Membrane filtration is an attractive for laundry wastewater treatment especially when aiming for detergent and water reuse. However, its performance is largely restricted by membrane fouling, especially when it is run under high and trans-membrane pressure (â³P) and in the sidestream configuration. The conventional treatment systems typically consist of multi-processes for removal of pollutants -including detergent- to meet the water discharge or reuse specification. This study assesses performance of a submerged membrane filtration under low â³P for treatment of real laundry wastewater, obtained from local laundry shop, aiming for detergent and water reuse. Results show that low â³P of as low as 0.05 bar offers the highest permeability of 297 Â± 15.3 Lmâ2 hâ1 barâ1 without significant membrane fouling. Increasing the â³P leads to decreasing trend in the permeability especially in the early stages of filtration. Aeration was found to be effective in enhancing hydraulic performance by 60 at rates >1 Lminâ1, below which offers ineffective foulant scouring impact. The membrane effectively removes chemical oxygen demand, total nitrogen, total phosphorus and turbidity of 52 , 13 , 65 and 97 respectively, and the system offers recovery of detergent from the spent laundry wastewater by 78 . Implementation of the concept in a laundry set-up can be done by treating wastewater from the washing cycle and reusing back the permeate for the following cycle. Our overall results suggest that the system is suitable to be applied for detergent and water reuse from wash cycle of industrial laundry. Â© 2020 Elsevier Ltd